Dyslipidemic hypertension: Distinctive features and cardiovascular risk in a prospective population-based study - Onat, A; Hergenç, G; Sari, I; Türkmen, S; Can, G; Sansoy, V (OXFORD UNIV PRESS, 2005)
Background: The prevalence, features, and risk of cardiovascular disease (CVD) in dyslipidemic hypertension (DH) was investigated in a prospective population-based study. Dyslipidemic hypertension was defined in terms of blood pressure, plasma triglycerides, and HDL-cholesterol consistent with the metabolic syndrome criteria of the National Cholesterol Education Program guidelines. High-normal or hypertensive values not meeting the other two criteria were designated as simple hypertensives (SH). Methods: A sample of 2225 men and women and free of CVD at baseline were followed up for a mean of 4.1 years. The proportions of DH, SH, and normotensives were 16%, 37%, and 47%, respectively. All persons with DH had metabolic syndrome by definition, whereas metabolic syndrome formed 44.6% of SH. Fatal and nonfatal CVD, diagnosed by clinical findings and Minnesota coding of resting electrocardiograms, developed in 166 subjects. Results: Compared to SH, sex- and age-standardized individuals with DH had significantly higher body mass index, apolipoprotein B, fasting insulin, glucose, and C-reactive protein levels, had higher prevalence of impaired fasting glucose and metabolic syndrome. Cox regression analysis revealed a 1.57-fold higher (confidence interval 1.08-2.28) hazard ratio (HR) for CVD in DH than in SH, after adjustment for sex, age, LDL-cholesterol, and smoking status. The sex- and age-adjusted HR of DH was furthermore 1.45-fold higher than the remaining subjects with metabolic syndrome (P =.096). Among persons with DH, age, presence of diabetes, and pulse pressure proved to be independent predictors for CVD. High LDL-cholesterol levels and fasting hyperinsulinemia were associated with borderline significantly elevated relative risks among dyslipidemic hypertensives. Conclusions: Dyslipidemic hypertension, prevailing in 1 of every 6 adults, implicates characteristic features, confers excess CVD risk compared to the remainder of hypertensives and carries half the attributable cardiovascular risk due to metabolic syndrome. (c) 2005 American Journal of Hypertension, Ltd.
Keywords: cardiovascular disease; dyslipidemic hypertension; hypertension; insulin resistance; metabolic syndrome; FAMILIAL COMBINED HYPERLIPIDEMIA; CORONARY HEART-DISEASE; LOW-CHOLESTEROL LEVELS; BLOOD-PRESSURE; INSULIN; UTAH; APOLIPOPROTEIN; IMPACT; Cardiovascular System & Cardiology